A STUDY OF CONTENT AND ORGANIZATION PRODUCED BY THE EIGHTH GRADE STUDENTS OF SMP N 1 KUDU JOMBANG IN WRITING RECOUNT TEXT - PRASTIWI, APRILIA (RETAIN : Journal of Research in English Language Teaching, 2013)
Penelitian ini bertujuan untuk mendeskripsikan kemampuan siswa kelas VIII SMPN 1 Kudu dalam menulis teks Recount khususnya pada komponen isi dan organisasi penulisannya. Untuk mendeskripsikan kemampuan siswa dalam menulis teks Recount dilakukan analisis dari hasil tulisan teks Recount siswa. Penelitian ini dirancang sebagai sebuah laporan dalam bentuk deskriptif qualitative dengan menggunakan rubrik penilaian untuk menunjukkan level kemampuan siswa dalam menulis teks Recount khususnya pada komponen isi dan organisasi penulisannya. Hasil penelitian ini menunjukkan bahwa sebagian besar kemampuan siswa dalam menulis teks Recount berada pada level average atau rata-rata. Kata Kunci: isi, organisasi penulisan, teks Recount. Abstract This study is conducted to describe the eighth grade students of SMPN 1 Kudu competence in writing recount text in terms of its content and organization. To describe the students’ competence in writing recount text, analysis on the students’ recount text composition was done. This study was designed as a report in the form of descriptive qualitative and used scoring rubrik to show the students competence level in writing Recount text in terms of its content and organization. The result of this study showed that most of the students’ competence in writing Recount text is in average level. Keywords: content, organization, Recount composition.